The female baroque in early modern English literary culture : from Mary Sidney to Aphra Behn - Waller, Gary F. (Gary Fredric), 1945- (Amsterdam : Amsterdam University Press, 2020)
The Female Baroque is a contribution to the revival since the 1980s of early modern women's writings and cultural production in English. Its originality is twofold: it links women's writing in English with the wider context of Baroque culture, and it introduces the issue of gender into discussion of the Baroque. The title comes from Julia Kristeva's study of Teresa of Avila, that 'the secrets of Baroque civilization are female'. [-]The book is built on a schema of recurring Baroque characteristics - narrativity, hyperbole, melancholia, kitsch, and plateauing, pointing less to surface manifestations and more to underlying ideological tensions. The crucial concept of the Female Baroque is developed in detail. Attention is then given particularly to Gertrude More, Mary Ward, Aemilia Lanyer, The Ferrar/Collet women, Mary Wroth, the Cavendish sisters, Hester Pulter, Anne Hutchinson, Margaret Cavendish and Aphra Behn, the latter two whose lives and writings point to the developing cultural transition to the Enlightenment.[-].
Frontmatter -- Table of Contents -- Introduction and Acknowledgements -- 1. The Labyrinthine Baroque -- 2. The Female Baroque -- 3. Catholic Female Baroque -- 4. Protestant Baroque -- 5. The Female Baroque in Court and Country -- 6. Lady Mary Wroth : The Countesse of Mountgomeries Urania and Pamphilia to Amphilanthus -- 7. From Baroque to Enlightenment: Margaret Cavendish and Aphra Behn -- Postscript -- About the Author -- Index
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed April 28, 2020).
JSTOR
Keywords: Pembroke, Mary Sidney Herbert, -- Countess of, -- 1561-1621.; Behn, Aphra, -- 1640-1689.; Behn, Aphra, -- 1640-1689; Pembroke, Mary Sidney Herbert, -- Countess of, -- 1561-1621; English literature -- Early modern, 1500-1700 -- History and criticism; Baroque literature -- History and criticism; Women and literature -- England -- History -- 17th century; Littérature baroque -- Histoire et critique; Femmes et littérature -- Angleterre -- Histoire -- 17e siècle.; Literary studies: c. 1500 to c. 1800.; British and Irish history; HISTORY -- Europe -- Great Britain -- Georgian Era (1714-1837); Baroque literature; English literature -- Early modern; Women and literature; England; 1500-1700; Baroque; Female Baroque; Julia Kristeva; Women's writing; early modern England; Criticism, interpretation, etc; History